Kolesterol dan Omega 9 Kuning Telur Ayam Petelur yang Mendapat Udang Mantis (Squilla empusa) Fermentasi dalam Pakan - Sri Suhermiyati (Agricultural Faculty, 2011)
Cholesterol and omega-9 fatty acid eggs yolks affected by mantis crustacean (squilla empusa) fermentation as a fish meal substitution in the diet of layer.ABSTRACT. The experiment was conducted to determine the effect of Squilla empusa fermentation as fish meal substitute in diet layer on cholesterol and omega-9 fatty acid yolk eggs. This research was conducted by completely randomized design (CRD) with 4 treatment and 5 replications. The treatments are P0 = 0% fermented Squilla empusa + 15% fish meal; P1 = 5% fermented Squilla empusa + 10% fish meal; P2 = 10% fermented Squilla empusa + 15% fish meal; and P3 = 15% fermented Squilla empusa + 0% fish meal. Cholesterol, Omega-9 fatty acid yolk eggs responding variables measured. The results of this study shows that the yolk cholesterol and omega - 9 was non significant (P0.05). Average of yolk cholesterol (ppm) and omega - 9 (gram) for P0; P1; P2; and P3 were 7.622; 9.200; 9.198; and 9.442; and omega 9 fatty acid yolk (%) were 18.404; 17.520; 19.230 and 19.456 respectively. Conclusion of this study (i) there are possibility using fermented Squilla empusa until 15% as fish meal substitute in diet of layers, (ii) there are good effect on eggs quality in term of cholesterol and Omega 9 fatty yolk.